The Effectiveness of Health Education Using Media Booklets and WhatsApp on Tuberculosis Patients at the Linggang Bigung Health Center, West Kutai Regency - Martha Lirung Hanye; Joko Sapto Pramono; Lukman Nulhakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main obstacle to controlling tuberculosis is knowledge and behavior to prevent transmission among at-risk contacts. Health education is needed to increase public knowledge. The purpose of this study was to analyze the effectiveness of health education using Booklet and WhatsApp media among tuberculosis sufferers. This type of research was quasi-experimental with a control group pre- and post-test approach, samples were taken from 41 tuberculosis patients who were currently being treated. Knowledge measurements were carried out before and after health education was carried out using Booklet and WhatsApp media. The analysis to test the effectiveness of the booklet and WhatsApp media used the Wilcoxon test. The Wilcoxon test results obtained a p-value of 0.046 (booklet) and a p-value of 0.014 (WhatsApp) lower than α = 0.05, meaning that both are effective in increasing knowledge, but Whatsapp media is more effective than booklet media.